(untitled) (Universal International Scientific Journal, 2026)
This article analyzes modern interactive teaching methods and innovative educational technologies used in teaching Russian in higher education. The relevance of this research is determined by the active digitalization of the educational space and age-related requirements for students’ communicative skills. The article explores the potential of using digital platforms, multimedia resources, technologies, blended learning, and elements of artificial intelligence in language education. It substantiates their impact on enhancing learning motivation, developing independent cognitive activity, and developing students’ communicative competence. It concludes that the comprehensive implementation of interactive and innovative technologies in Russian language teaching at universities is beneficial.